2017
DOI: 10.1371/journal.pone.0188437
|View full text |Cite
|
Sign up to set email alerts
|

Community prevalence of chronic respiratory symptoms in rural Malawi: Implications for policy

Abstract: BackgroundNo community prevalence studies have been done on chronic respiratory symptoms of cough, wheezing and shortness of breath in adult rural populations in Malawi. Case detection rates of tuberculosis (TB) and chronic airways disease are low in resource-poor primary health care facilities.ObjectiveTo understand the prevalence of chronic respiratory symptoms and recorded diagnoses of TB in rural Malawian adults in order to improve case detection and management of these diseases.MethodsA population proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 20 publications
(25 reference statements)
1
30
2
1
Order By: Relevance
“…As already mentioned in our study, women using solid fuel for cooking in the living house showed 1.89 times higher odds of having at least one respiratory symptom compared with cleaner energy users, which is consistent with previous studies [26,27,31,33,37]. Meanwhile, the distribution of at least one of the respiratory symptoms was nearly equal among those having a window in the cooking area and those having only the door as a means of ventilation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As already mentioned in our study, women using solid fuel for cooking in the living house showed 1.89 times higher odds of having at least one respiratory symptom compared with cleaner energy users, which is consistent with previous studies [26,27,31,33,37]. Meanwhile, the distribution of at least one of the respiratory symptoms was nearly equal among those having a window in the cooking area and those having only the door as a means of ventilation.…”
Section: Discussionsupporting
confidence: 92%
“…Both the prevalence of the respiratory symptoms and the exposure to the solid fuels were high compared with another study from Rwanda [31]. Except for breathlessness, which was found to be higher in that study, the prevalence of other respiratory symptoms among never-smokers were nearly doubled in this study when compared with other Sub-Saharans studies [31][32][33]. Not only did all rural women in the present study use solid fuel as the only energy source, most of them also had a larger family size, poor ventilation, animals in the same house and performed cooking in the main living room.…”
Section: Discussioncontrasting
confidence: 58%
“…Another study by Banda reported that 22.5% of the study population of Malawi had at-least one respiratory symptoms and chronic cough was the most commonest symptom. 10 Both these studies reported higher prevalence of chronic respiratory symptoms compared to the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…The findings from this qualitative study are being used to complement the data obtained in the Triage II Plus project (Trial Registration Number: NCT02127983) [13] in which it is nested. Triage II Plus, which is being carried out by the Research for Equity And Community Health (REACH) Trust in Malawi, is a trial investigating the approaches to improve detection and management of chronic airways disease.…”
Section: Research Objectivesmentioning
confidence: 99%
“…The fieldwork for this study was carried out in April 2018 alongside the Triage II Plus Endline Survey [13] which provided the data for selection and recruitment of participants. In order to coordinate with local research assistants, and because the data collection for the current study was conducted at the same time as that of the Triage II Plus project, the first 12 survey respondents who were considered to meet our inclusion criteria and could be located using the household GPS coordinates provided, were recruited.…”
Section: Recruitmentmentioning
confidence: 99%